Reflection of generation leadership marketing strategies pillars to enhancing customer value : Field study at Asia Cell Telecommunications Company - A. Raouf, Raad (Iraqi Journal for Administrative Sciences, 2024)
The research sought to identify the implications of the generation leadership marketing strategy as a qualitative shift in the contexts of dealing with the customer’s needs and desires away from traditional frameworks and ready-made models that no longer work in dealing with the contemporary customer, as this strategy represents a new starting line and a modern approach to dealing with the changes of the era and its secrets On the totality of individual needs and preferences Which has become characterized by great diversity and overlap between the requirements of generations unlike what was the case in the past, so the current study dealt with the presentation of the contents of this strategy and determining its impact in achieving customer value based on the fierce competition faced by telecommunications companies in general and the research company in particular in their quest to provide value Distinctive for the customer, which represents a challenge and a problem that requires the adoption of unconventional frameworks of thinking. Perhaps the most prominent of these frameworks is what is included in the generation leadership strategy. The importance of the research is manifested in addressing contemporary issues that require research and scrutiny for their role in improving companies’ performance by enhancing the quality of their services by providing value to the customer, through an inductive and analytical approach that dealt with those variables theoretically as well as trying to project the dimensions of these two variables in the field to show the relationship and influence between them to test the hypotheses that were adopted Which was tested using the statistical software (spss v.25 ) based on the data that was collected for the research sample represented by the employees of the Asia Cell Communications Company in the Nineveh Governorate and based on the questionnaire form. The value of the customer at the macro and micro levels, in light of the conclusions, a set of proposals were presented, the most important of which is the need for the company in question to study the preferences of customers through survey studies in order to be able to provide a distinct value.